Pathobiomes Differ between Two Diseases Affecting Reef Building Coralline Algae - Meistertzheim, Anne-Leila; Nugues, Maggy M.; Quéré, Gaëlle; Galand, Pierre E. (Frontiers in Microbiology, 2017)
Crustose coralline algae (CCA) are major benthic calcifiers that play crucial roles in coral reef ecosystems. Two diseases affecting CCA have recently been investigated: Coralline White Band Syndrome (CWBS) and Coralline White Patch Disease (CWPD). These diseases can trigger major losses in CCA cover on tropical coral reefs, but their causative agents remain unknown. Here, we provide data from the first investigation of the bacterial communities associated with healthy and diseased CCA tissues. We show that Neogoniolithon mamillare diseased tissues had distinct microbial communities compared to healthy tissues and demonstrate that CWBS and CWPD were associated with different pathobiomes, indicating that they had different disease causations. CWBS tissues were composed of opportunistic bacteria, and the origin of the disease was undetermined. In contrast, a vibrio related to V. tubiashii characterized the CWPD pathobiome, suggesting that it could be a putative disease agent and supporting the case of a temperature dependent disease associated with global warming.